Interactions between microplastics, pharmaceuticals and personal care products: Implications for vector transport - Atugoda, Thilakshani; Vithanage, Meththika; Wijesekara, Hasintha; Bolan, Nanthi; Sarmah, Ajit K.; Bank, Michael S.; You, Siming; Ok, Yong Sik (Environment international, 2021)
[Display omitted] •Pharmaceuticals and personal care products co-exists with microplastics in water.•Microplastic can act as a vector for flow and transport of hydrophilic organics.•Salinity, pH, dissolved organics, polymer, and PPCP type influence the sorption mechanism. Microplastics are well known for vector transport of hydrophobic organic contaminants, and there are growing concerns regarding their potential adverse effects on ecosystems and human health. However, recent studies focussing on hydrophilic compounds, such as pharmaceuticals and personal care products (PPCPs), have shown that the compounds ability to be adsorbed onto plastic surfaces. The extensive use of PPCPs has led to their ubiquitous presence in the environment resulting in their cooccurrence with microplastics. The partitioning between plastics and PPCPs and their fate through vector transport are determined by various physicochemical characteristics and environmental conditions of specific matrices. Although the sorption capacities of microplastics for different PPCP compounds have been investigated extensively, these findings have not yet been synthesized and analyzed critically. The specific objectives of this review were to synthesize and critically assess the various factors that affect the adsorption of hydrophilic compounds such as PPCPs on microplastic surfaces and their fate and transport in the environment. The review also focuses on environmental factors such as pH, salinity, and dissolved organics, and properties of polymers and PPCP compounds, and the relationships with sorption dynamics and mechanisms. Furthermore, the ecotoxicological effects of PPCP-sorbed microplastics on biota and human health are also discussed.